Factors Influencing Receptive Language Skills in Preschoolers: The Role of Intelligence, Social Environment, and Family Background - Hikmatuzzohrah, Shofia; Syamsudin, Amir; Maryatun, Ika Budi (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
Receptive language ability in early childhood is an important indicator of language development, influenced by various factors. However, the understanding of the factors that contribute most significantly to receptive language remains limited, warranting further investigation. This study aims to confirm the factors affecting receptive language and identify the most significant contributors to children's receptive language development. This research employs a quantitative method with an ex post facto design. The sample consists of 87 children from five kindergartens. Data were collected using a 1-5 Likert scale questionnaire and analyzed through descriptive analysis and SEM-PLS, including CFA, t-test values, p-values, and bootstrapping, using SPSS 25.0 and SmartPLS software. The results of the study indicate that the intelligence construct has a significant effect on receptive language, contributing 62.8% (t = 20.543 > 1.9; p-value = 0.00 < 0.05). The social and cultural environment construct has a significant impact on receptive language, contributing 22.5% (t = 6.707 > 1.9; p-value = 0.00 < 0.05). The family environment construct also significantly influences receptive language, contributing 25.3% (t = 6.991 > 1.9; p-value = 0.00 < 0.05). The most influential factor on receptive language is intelligence, with the highest contribution of 62.8%. The conclusion of this study is that intelligence is the primary factor influencing children's receptive language ability, followed by the social and cultural environment and the family environment.